2010
DOI: 10.1016/j.bioorg.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,6-dideoxy-3-fluoro-2-keto-β-d-glucopyranosyl analogues of 5-fluorouracil, N6-benzoyl adenine, uracil, thymine, N4-benzoyl cytosine and evaluation of their antitumor activities

Abstract: The synthesis of the unsaturated 4,6-dideoxy-3-fluoro-2-keto-beta-d-glucopyranosyl nucleosides of 5-fluorouracil (6a), N(6)-benzoyl adenine (6b), uracil (6c), thymine (6d) and N(4)-benzoyl cytosine (6e), is described. Monoiodination of compounds 1a,b, followed by acetylation, catalytic hydrogenation and finally regioselective 2'-O-deacylation afforded the partially acetylated dideoxynucleoside analogues of 5-fluorouracil (5a) and N(6)-benzoyl adenine (5b), respectively. Direct oxidation of the free hydroxyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…[12,13] In recent years, pyranosyl nucleosides are viewed as important modifications of natural nucleosides, offering promising avenues in the development of novel bioactive agents with promising therapeutic potential. [14][15][16][17][18][19][20][21][22][23][24] In our previous investigations, we demonstrated that base-modified pyranonucleosides rank among the most potent glycogen phosphorylase (GP) [25,26] and thymidylate synthase (TS) [27] inhibitors, and were endowed with a pronounced cytostatic and antiviral action. [28] As a continuation of this research and based on the pharmacological properties of thiopurine analogues, we now report the synthesis and biology of new thiopurine pyranonucleosides via glycosylation of mercaptopurine and thioguanine pyranonucleosides bearing D-glucose, D-galactose, D-xylose, D-mannose, and D-lyxose as sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] In recent years, pyranosyl nucleosides are viewed as important modifications of natural nucleosides, offering promising avenues in the development of novel bioactive agents with promising therapeutic potential. [14][15][16][17][18][19][20][21][22][23][24] In our previous investigations, we demonstrated that base-modified pyranonucleosides rank among the most potent glycogen phosphorylase (GP) [25,26] and thymidylate synthase (TS) [27] inhibitors, and were endowed with a pronounced cytostatic and antiviral action. [28] As a continuation of this research and based on the pharmacological properties of thiopurine analogues, we now report the synthesis and biology of new thiopurine pyranonucleosides via glycosylation of mercaptopurine and thioguanine pyranonucleosides bearing D-glucose, D-galactose, D-xylose, D-mannose, and D-lyxose as sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Several pyrimidine derivatives exhibit diverse pharmacological activities as antiviral [1,2,3,4,5,6,7,8,9], anti-inflammatory [10,11,12], and antimalarial agents [13,14,15]. Many pyrimidines have been demonstrated to possess anticancer [16,17,18,19,20,21], antituberculosis [22] and anti-allergic [23] activities. Moreover, several pyrimidine derivatives have been reported as antithyroid [24] and antimicrobial agents [25,26,27,28,29,30], as well as human thymidine and uridine phosphorylase inhibitors [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The uracil scaffold and its derivatives are known to have a wide spectrum of bioactivities that have helped chemists and biologists to move forward with harmony. The nucleophilic nature of the C-5 position of uracil and its derivatives is well-known, and its reactivity is greatly influenced by the nature of substituents in the uracil skeleton. In fact, this is one of the strategies adopted for the synthesis of bioactive 5-substituted uracil derivatives .…”
Section: Introductionmentioning
confidence: 99%